Deadly impalement of a blue shark Prionace glauca by a swordfish Xiphias gladius - PENADÉS-SUAY, J.; TOMÁS, J.; AZNAR, F. J. (Mediterranean Marine Science, 2017)
In September, 2016, an adult female blue shark (Prionace glauca) 247 cm long stranded alive on the coast of Valencia (Spain, Western Mediterranean) but died shortly afterwards. The necropsy revealed ongoing pregnancy, with 65 embryos in early stage of development, and a healthy condition with no signs of starvation. Two fishing hooks surrounded by scarred tissue were detected in the mandible, indicating past interaction with fisheries. In addition, a fragment of the tip of a swordfish (Xiphias gladius) rostrum (length: 18 cm long, width: 0.5 cm (distal) and 3 cm (proximal)) was removed from the animal. The fragment had pierced the head producing an incision of 3.5 cm close to the left eye, crossing the head anterior to the pre-orbital process. No apparent damage was observed in the olfactory capsule or the eye, but the fragment had penetrated both sides of the skull causing extensive lesions in the brain, which were inferred to be the cause of death. Allometric analysis suggested that the swordfish was ca. 110 cm long, corresponding to a juvenile 1-2 yrs old. Swordfish had previously been reported driving their rostrum into pelagic sharks, allegedly as a defensive strategy. However, this is the first report of impalement as the direct cause of death in blue sharks.